2003
DOI: 10.1002/pd.561
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cortical gyrus and sulcus formation using MR images in normal fetuses

Abstract: Our classification is useful for the assessment of fetal cerebral maturation during the third trimester of pregnancy and may contribute to the prenatal diagnosis of developmental delay of the gyrus and sulcus formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 18 publications
(27 reference statements)
0
22
0
1
Order By: Relevance
“…In research into the cerebral effects of prematurity, qualitative scales of gyration have normally been used to estimate the cerebral maturation of the fetuses or the premature newborn. 7 Scales of this kind have generally been useful for identification of cerebral maturation stage, detection of major neurologic abnormalities, and prediction of neurologic outcomes of preterm newborns, but they are unable to determine mild cerebral dysfunctions. Using a whole-cortex convolution index, a previous study found that preterm infants significantly differed from controls born at term.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In research into the cerebral effects of prematurity, qualitative scales of gyration have normally been used to estimate the cerebral maturation of the fetuses or the premature newborn. 7 Scales of this kind have generally been useful for identification of cerebral maturation stage, detection of major neurologic abnormalities, and prediction of neurologic outcomes of preterm newborns, but they are unable to determine mild cerebral dysfunctions. Using a whole-cortex convolution index, a previous study found that preterm infants significantly differed from controls born at term.…”
Section: Resultsmentioning
confidence: 99%
“…However, MRI has become an important source for identifying sulci and gyral abnormalities. [6][7][8][9][10][11][12][13][14][15] Magnetic resonance (MR) studies demonstrated that brain maturation starts in the central area and proceeds toward the parieto-occipital cortex. The frontal cortex develops last.…”
mentioning
confidence: 99%
“…In this context, one must carefully evaluate which gyral landmarks are established early enough in cortical development to allow their reliable identification throughout different stages of gyrification. For example, the medium and inferior temporal sulci appear around 34 w PMA (Abe et al, 2003) and are therefore not defined at an age where MR scans of preterm infants may be analyzed. Recent approaches have investigated the feasibility of DTI parcellation in adults (Klein et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This classification focuses on frontal and occipital sulcation and gyration, observing the folds of the insular cortex at the stage 4 only (37-39 GWs). The development of the cerebral cortex was later classified into eight stages using MR images in the Ac-Pc plane, with special attention to the frontal and temporal lobes (Abe et al 2003).…”
Section: Chronological Classification Of Macroscopical Developmentmentioning
confidence: 99%